Metastatic breast tumor as a differential diagnosis for clival lesion - Anna Paula Auada Kopaz; Thais Potter; Viviane Martori Pandini; Edmir Américo Lourenço (Revista Portuguesa Otorrinolaringologia e Cirurgia de Cabeça e Pescoço)
M. M. J. O. S., a 60-year-old woman, presenting with progressive paresthesia on the left side of her face, for the past 4 months. No nasal, otological or ocular complaints. Physical exam showed no alterations. Four months ago, a MRI was performed, showing a median and paramedian left expansile lesion of probable neoplastic nature in the clivus, located medially and paramedially to the left. A past history of breast carcinoma personal history, patient refers tumor in left breast 9 years ago, with histopathological exams pointing to invasive ductal carcinoma with compromised margins after surgery. Patient underwent treatment and follow-up, with no recurrence of the tumor until the present moment. Two years and four months ago, patient presented with occipital headache, face drooping and left body paresthesia. Seven months ago, a similar episode occurred, with normal MRI and a hypothesis of Transient Ischemic Attack. Fibroscopic laryngoscopy showed a tumor invading the rhinopharynx, and a left sphenoid sinus biopsy was performed, via endonasal approach. The pathological exam showed a poorly differentiated invasive malignant neoplasic lesion, poorly differentiated. The immunohistological analysis presented similar positive markers as to the previous breast tumor in the patient’s history.